2005
DOI: 10.1359/jbmr.041207
|View full text |Cite
|
Sign up to set email alerts
|

Bone Resorption and Osteoporotic Fractures in Elderly Men: The Dubbo Osteoporosis Epidemiology Study

Abstract: Among the potential risk factors for fragility fractures, bone turnover is considered an important determinant. In a case-cohort control study of 151 elderly men followed prospectively over 6.3 years, high bone resorption as assessed by S-ICTP was associated with increased risk of osteoporotic fracture, independent of BMD. Combining measurements of BMD and bone turnover may improve fracture prediction in elderly men.Introduction: Approximately one-third of osteoporotic fractures occur in men. Among the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(78 citation statements)
references
References 56 publications
(68 reference statements)
3
70
0
5
Order By: Relevance
“…Differences in the bone turnover markers (BTM) levels between men who did or did not have MetS were inconsistent. Since the association between BTM and fracture risk in men is doubtful, (50)(51)(52)(53) differences in bone turnover rate cannot explain lower fracture risk in men with MetS. History of fracture and of fall is associated with a higher risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the bone turnover markers (BTM) levels between men who did or did not have MetS were inconsistent. Since the association between BTM and fracture risk in men is doubtful, (50)(51)(52)(53) differences in bone turnover rate cannot explain lower fracture risk in men with MetS. History of fracture and of fall is associated with a higher risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…(25) A recent report found that high bone resorption was associated with increased fracture risk in older men, independent of BMD. (28) The recent literature suggesting that ghrelin may play a role in short-term bone health is currently based on short-term animal studies only.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that TRAP-5b was negatively correlated with Ca in women (β = −0.059, P = 0.039). Because it is well known that ALP is a classical marker for osteoid formation and calcification, and that Ca is important to maintain bone density and is lost with aging especially in women (Hannan et al 2000;Izumotani et al 2003;Meier et al 2005;Lanham-New 2008;Hien et al 2008), our present results suggest that TRAP-5b is a sensitive marker for screening for BMD in the general population of elderly individuals, especially women.…”
Section: Discussionmentioning
confidence: 60%